The Effect of Talking Stick on Students' Islamic Religious Education Learning Outcomes - Alfaridzi, Eko; Azima, Fauzan; Dwi, Gebi Sintia; Erizal, Erizal; Metriadi, Metriadi (Suluah Pasaman, 2024)
The low learning outcomes of Islamic Religious Education (PAI) cause problems for students who do not dare to express their opinions in class. This study aims to understand the effect of the Talking Stick learning model on students' PAI learning outcomes. This research is a field research with a quantitative research method that uses an experimental approach. Sampling using purposive sampling technique. Data collection in this study used test instruments. Data processing and analysis using statistical data. So obtained the results of the Talking Stick learning model with an average value of 81.6 learning outcomes.